Structure and physical technical and tactical training handball players aged 10-11 years - Palagin, A. A. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to study the structural and functional relationships, physical, technical and tactical training handball aged 10-11 years.